TI_GERICHTE 12.2006.56 vom 31. Mai 2006 , azione di disconoscimento del debito in procedura appellabile - termine d'inoltro - TI Tribunale d'appello (2006)
azione di disconoscimento del debito in procedura appellabile - termine d'inoltro